Between Past and Future - 1/3
Recording of the international conference "Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" organized by CEU and the University of Maryland, held at CEU between 26th and 28th of March, 1999. Contains the second part of the Q&A session with Professor Sorin Antohi (Academic Pro-Rector at CEU), Professor Vladimir Tismăneanu (Maryland University) and Dr. István Teplán (Executive Vice President of CEU). Contains also recordings from the first conference panel entitled “1989 and its Aftermath through the Eyes of the Media” where the participants were American and Hungarian print, television and radio journalist who covered the events in 1989. The introductory remarks for this panel were delivered by former US Ambassador to Hungary and Chair of the CEU International Council, Donald Blinken. The panel was chaired by Kati Marton (author and journalist). The members of the panel were R. W. Apple Jr. (Chief Correspondent, “New York Times”), Barrie Dunsmore (Former Senior Correspondent, ABC News), James Carney (Political Correspondent, “Time Magazine”), Flora Lewis (Senior Columnist, “New York Times” Syndicate), Ambassador Richard Holbrooke (U.S. Special Envoy to Yugoslavia) and György Bolgár (Journalist and Broadcaster, Hungarian Radio). Speeches recorded on this tape belong to R. W. Apple Jr. and Barrie Dunsmore.